2004
DOI: 10.1016/j.rmed.2003.12.014
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of conventional nighttime with automatic or manual daytime CPAP titration in unselected sleep apnea patients: study of the usefulness of daytime titration studies

Abstract: Daytime CPAP titration studies with full polysomnography have been successfully performed in patients with severe sleep apnea-hypopnea syndrome (SAHS). The implementation of daytime studies in unselected SAHS patients could help to reduce the waiting lists for CPAP titrations. The main purpose of this study was to compare the effectiveness of conventional versus manual or automatic daytime CPAP titration in unselected patients with SAHS. Ninety-three consecutive patients with SAHS in whom CPAP was indicated we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 26 publications
2
18
0
2
Order By: Relevance
“…The mean pressure of auto‐CPAP tends to be lower than fixed‐CPAP in general, but some auto‐CPAP devices may not respond adequately 32,33 . While some studies showed certain brands of auto‐CPAP devices to be superior to fixed‐CPAP in improving clinical parameters and compliance, the results are inconsistent 18–26 (Table 4). In a bench study, different brands of auto‐CPAP devices were found to perform differently 34 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mean pressure of auto‐CPAP tends to be lower than fixed‐CPAP in general, but some auto‐CPAP devices may not respond adequately 32,33 . While some studies showed certain brands of auto‐CPAP devices to be superior to fixed‐CPAP in improving clinical parameters and compliance, the results are inconsistent 18–26 (Table 4). In a bench study, different brands of auto‐CPAP devices were found to perform differently 34 …”
Section: Discussionmentioning
confidence: 99%
“…Guidelines on the use of auto‐CPAP are available from the Task Force of the Standards of Practice Committee of the American Academy of Sleep Medicine 17 . Numerous studies have compared different auto‐CPAP devices against fixed‐CPAP for treatment purposes, but the results are inconsistent 18–26 . This study compared the efficacy of auto‐ versus fixed‐CPAP in improving sleepiness and health status in Chinese patients in Hong Kong with severe OSA.…”
Section: Introductionmentioning
confidence: 99%
“…Compliance with treatment and symptom improvement were similar at 3 months among 93 OSAS patients whether titrated to CPAP by conventional manual in-lab night titration, or manual or autodaytime titration after sleep deprivation, though pressure selected with auto-CPAP was significantly higher (Lloberes et al, 2004). In patients with high within-night variability in pressure requirements, the use of auto-CPAP compared with fixed-pressure CPAP did not confer compliance advantage and both methods were equivalent in terms of AHI reduction; however, mean Epworth Sleepiness Scale score was slightly and significantly lower on auto-CPAP (Noseda et al, 2004).…”
Section: Autotitrating Continuous Positive Airway Pressurementioning
confidence: 90%
“…Subsequently, using older generation APAP devices, investigators have demonstrated that the “fixed” CPAP pressure determined by APAP therapy can either be the same, greater, or less than that derived from attended PSG (1720). Such a simplistic comparison, however, should probably not be made considering that; the gold standard itself suffers from inherent limitations – cost, inconvenience of electrode placements, laboratory versus home environment, and limited “one-night” sampling.…”
Section: Scientific Evidencementioning
confidence: 99%